New Skills for New Century : Informing Regional Policy - Shmis, Tigran (World Bank, Washington, DC, 2021)
As part of the World Bank’s analytical support program in Russia, the team has been working with their Russian counterparts on collecting and analyzing data in order to gather evidence to inform coherent policies and strategies for creating modern schools and for promoting 21st-century teaching and learning in Russia. Both goals are being pursued through a series of national projects aimed at: (i) modernizing teaching and learning; (ii) putting Russia in the top 10 countries in terms of scores on international assessments; and (iii) expanding school infrastructure to ensure full-day schooling throughout the country. This new report presents a rigorous analysis of the data collected as part of the Trends in Mathematics and Science Study (TIMSS) in 2019 complemented by data on Russia from the OECD’s School User Survey (SUS), which was also fielded in 2019. The team added the SUS to the study as part of its collaboration with its Russian counterparts. The total sample represents all general education systems in the Russian Federation. This report also includes data from Information and Communication (IC) Literacy Test7 conducted in 2020 combined with the SUS. The two datasets are not related but both cover 21st-century skills and Russian students. This report analyzes the various 21st-century skills that it was possible to analyze using data from the TIMSS and IC Literacy Test. The analysis provides descriptive statistics related to the learning environments and teaching practices in Russia and draws some correlations between learning environment variables and learning outcomes. Furthermore, the study shows how different teaching styles affect student learning in the mathematics, science, and cognitive (reasoning and applying) domains of TIMSS. The team also analyzed the wellbeing construct included in TIMSS 2019. They found that the cognitive domains of reasoning and applying were well aligned with the 21st-century skills that can be measured directly by TIMSS. This study also attempts to use self-reported data from TIMSS student and teacher questionnaires and construct measures to stimulate teaching and learning activities related to 21st-century skills development. The study also assesses the impact of such measures on student performance across subject and cognitive domains. In exploring IC literacy and ICT technology in schools, the report analyzes key characteristics of the school environment, the use of ICT in schools, the use of technology by teachers with different mindsets towards modern education, and students' performance on the IC Literacy Test with an analysis of the context of the questions.